The spectrum of biopsy-proven glomerular diseases in a tertiary Hospital in Southern Brazil - Gustavo Gomes Thomé; Talissa Bianchini; Rafael Nazario Bringhenti; Pedro Guilherme Schaefer; Elvino José Guardão Barros; Francisco Veríssimo Veronese (BMC Nephrology, 2021)
Abstract Background The prevalence and distribution of glomerular diseases differ among countries, and the indication to perform a kidney biopsy varies among centres. In this study, we assessed the prevalence of primary and secondary glomerulopathies based on histological diagnoses, and the correlation between glomerulopathies and demographic and clinical data was evaluated. Methods In this study, 1051 kidney biopsies were retrospectively reviewed between 2000 and 2018. Patient demographic, clinical and laboratory data were assessed. The prevalence of primary glomerulonephritis (PG) and secondary glomerulopathies (SG), as well as tubulointerstitial diseases (TIDs), hereditary nephropathies (HNs) and other diagnoses, were determined. The frequency of primary and secondary glomerulopathies was evaluated by age group, and the temporal variation in frequencies across three time periods (2000-2005, 2006-2011, and 2012-2018) was reported. Results The prevalence of SG predominated (52.4%), followed by PG (29.6%), other diagnoses (10.7%), TID (6.6%) and HN (1.1%). Among the primary forms of glomerular disease, focal segmental glomerulosclerosis (FSGS) was the most common (37.3%), followed by IgA nephropathy (IgAN, 24.4%), membranous nephropathy (MN, 18.6%) and minimal change disease (MCD, 8.4%). Lupus nephritis (LN, 41.1%) was most common in patients with SG, followed by diabetic kidney disease (DKD, 17.8%), systemic vasculitis (SV, 10.2%) and secondary FSGS (2nd FSGS, 10%). Nephrotic syndrome was the most common clinical presentation in patients with PG and also in patients with DRD and 2nd FSGS, whereas in patients with IgAN and SV, nephritic syndrome was the main presentation. For the age group between 18 and 50 years, LN, FSGS and IgAN predominated; for patients aged between 51 and 65 years, the proportion of DKD and 2nd FSGS increased, and SV was more common in patients > 65 years. The temporal variation in PG across the three time periods showed a statistically significant increase in IgAN (p = 0.001) and a reduction in FSGS over time (p < 0.001). In SG, there was a reduction in LN (p = 0.027) and an increase in DKD (p < 0.001) over time, with a tendency for 2nd FSGS to decrease over time (p = 0.053). Conclusions In the studied kidney biopsy registry, FSGS and IgAN were the most prevalent diagnoses in patients with PG, and LN and DKD were the most prevalent in patients with SG. Nephrotic syndrome was the major indication for biopsy. When comparing the temporal variation in glomerulopathies, there was a reduction in FSGS and an increase in IgAN in patients with PGs over time, and for patients with SGs, there was a reduction in LN with an increase in cases of DKD over time.